Helmintos de populações simpátricas de algumas espécies de anfíbios anuros da família Leptodac tylidae - Fabio, Sueli Pontes de (1979)
A survey was made of the helminth parasites found in populations of 8 different species of leptodactylid frogs living in a forested area of the original "Horto Florestal de Santa Cruz", at present the "Estação Florestal de Experimentação Engenheiro Agrônomo Maria Xavier", Municipality of Itaguaí, Rio de Janeiro State, with a view to comparing parasitism in sympatric populations of anurans related phylogenetically. Necropsies were carried out on 170 specimens, representing the following species of anurans: Leptodactylus ocellatus (Linnaeus, 1758), L. sibilatrix (Wied, 1824), L. mystaceus (Spix, 1824) L. mystacinus (Burmeister, 1861), L. caliginosus Girard, 1853, L. marmoratus (Steindachner, 1867), Phyalaemus signiferus (Girard, 1853) and P. soaresi Izecksohn, 1965. A total of 1,098 helminths were obtained, representing the following species: Mesococliun monas (Rudolphi, 1819) Oxyascaris oxyascaris Travassos, 1920, Pteroxyascaris caudacutus Freitas, 1958, Spironoura mascula (Rudolphi, 1819), Aplectana membranosa (Schneider, 1866), A. lopesi Silva, 1954, Neyraplectana sp., Cosmocerca parva Travassos, 1925, Rhabdias sp. Physaloptera sp. and Centrorhynchus sp. Redescriptions were made of the helminths, as well as an analysis of some aspects of their systematics. Certain features of the parasitism found are discussed, such as differences between the host species, competition between and within the species of helminths, indices of parasitism, preferential sites, seasonal frequency and factors influencing the infection. Synonymity was established between Oxyascaris oxyascaris Travassos, 1920 and necopinus Freitas, 1958 and between Cosmocerca parva Travassos, 1925, and C. freitasi Silva, 1954. Associations were noted between anurans and helminths as follows: L. ocellatus (O. oxyascaris, S. Mascula, C. parva, Rhabdias sp.), L. sibilatrix (M. monas, Pt. caudacutus, C. parva), L. mystaceus (M. monas, O. oxyascaris, Pt. Caudacutus, C. parva, Physaloptera sp., Centrorhynchus sp.), L. mystacinus (M. monas, A. membranosa, Centrorhynchus sp.), L. caliginosus (S. macula, C. parva, Physaloptera sp., Centrorhynchus sp.), L. marmoratus (Neyraplectana sp., C. parva, Physaloptera sp., Centrorhynchus sp.) P. signiferus (O. oxyascaris, A. lopesi, Neyraplectana sp., C. parva, Physaloptera sp., Centrorhynchus sp.) and P. soaresi (O. oxyascaris, C. parva, Physaloptera sp., Centrorhynchus sp.). Parasitism by nematodes was more frequent than by acanthocephalans or trematodes, and the level of infection was highest in summer and spring. Differences in behaviour between the hosts were considered as factors influencing differences in the nature and degree of parasitism recorded.